Potential of agroforestry systems in carbon sequestration in India - S K DHYANI; ASHA RAM; INDER DEV (The Indian Journal of Agricultural Sciences, 2016)
Various institutions are working for lowering the CO2 concentration through different strategies like reduction in energy use, developing low or no-carbon fuel technologies, CO2 sequestration by forestry/agroforestry and engineering techniques. Among all the techniques, agroforestry was recognized as one of the important means to reduce CO2 emissions as well as enhancing carbon sinks. Agroforestry provides unique opportunity to combine the twin objectives of climate change adaptation and mitigation. In India, area under agroforestry was estimated at 25.3 m ha, which can further be increased up to a considerable level. Recent studies under various agroforestry systems in diverse ecological conditions emphasized that agroforestry systems increase and store carbon stocks in above ground biomass and in soil and also has an important role in increasing livelihood security and reducing vulnerability to climate change. In India carbon sequestration potential of agroforestry systems is estimated between 0.25 - 76.55 and 0.01 to 0.60 Mg C/ha/yr for tree and crop component, respectively. The contribution of agroforestry in soil carbon sequestration varied between 0.003 to 3.98 Mg C/ha/yr. The total C sequestered in each component differs greatly depending on region, types of -species, -system, -site quality, and previous land-use. The review indicates that agroforestry systems in addition to accumulate and sequester carbon, provide an excellent opportunity to increase the tree cover to a level of 33% of the total geographical area of the country as desired by the National Forest Policy.